Legal Consciousness in the Polish People’s Republic: The Epistemological Roots of the High Consensus Concept - Tomasz Raburski (Acta Universitatis Lodziensis Folia Iuridica)
The paper explores the case of legal consciousness research in Poland during the period from the 1960s to the 1990s, focusing on its epistemic foundations. Three distinct traditions – Western, Soviet, and Polish – are identified, each with varying levels of scholarly consensus and diverse sources of that consensus. The study offers a concise analysis of different conceptualisations of legal consciousness. The methodological framework of the sociology of law during this era is examined, drawing from Carl. E. Schorske’s concept of “new rigorism”. The research observes a certain feature of the Polish legal consciousness research – a prevalence of tripartite distinctions. The reasons behind this phenomenon are explored and interpreted as a consequence of deep epistemic assumptions rooted in positivism.